Event management of students academic award at Academy of Contemporary Islamic Studies (ACIS) / Norelleza Syuhada Ab Rahim. - Ab Rahim, Norelleza Syuhada (2019)
Student academic award is conducted every semester. In UiTM, the student academic award consists of Dean List Award, Vice-Chancellor Award and Special Award. This study will review on (1) to study the event management of student academic award event, (2). to investigate the issue and challenges in managing the student academic award event,(3). to propose recommendations for improvement in future The qualitative method by collecting data through interview had been used to achieve all the objectives. The interview involving three students and two lecturers who have experience in organising and handling student academic award event. Based on the information from the interview, preparation of proposal is the most important element before organising the event.